2021
DOI: 10.3389/fsurg.2021.666158
|View full text |Cite
|
Sign up to set email alerts
|

Nodal Upstaging Evaluation After Robotic-Assisted Lobectomy for Early-Stage Non-small Cell Lung Cancer Compared to Video-Assisted Thoracic Surgery and Thoracotomy: A Retrospective Single Center Analysis

Abstract: Introduction: The standard surgical procedures for patients with early-stage NSCLC is lobectomy-associated radical lymphadenectomy performed by using the thoracotomy approach. In the last few years, minimally invasive techniques have increasingly strengthened their role in lung cancer treatment, especially in the early stage of the disease. Although the lobectomy technique has been accepted, controversy still surrounds lymph node dissection. In our study, we analyze the rate of upstaging early non-small cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 35 publications
3
13
0
1
Order By: Relevance
“…In our hospital, mediastinal LNs were systemically assessed by using thoracic CT and PET-CT, and invasive approaches including EBUS-TBNA and mediastinoscopy were further applied when necessary to minimize the incidence of occult N2 disease. Moreover, in our study, the incidence of occult N2 disease in RATS, VATS, and OL groups was 4.12%, 4.12%, and 8.25%, respectively, which was consistent with many previous studies (11,32,(37)(38)(39)(40). Our results also showed that the three groups had comparable incidences of postoperative lymph nodal upstaging.…”
Section: Discussionsupporting
confidence: 92%
“…In our hospital, mediastinal LNs were systemically assessed by using thoracic CT and PET-CT, and invasive approaches including EBUS-TBNA and mediastinoscopy were further applied when necessary to minimize the incidence of occult N2 disease. Moreover, in our study, the incidence of occult N2 disease in RATS, VATS, and OL groups was 4.12%, 4.12%, and 8.25%, respectively, which was consistent with many previous studies (11,32,(37)(38)(39)(40). Our results also showed that the three groups had comparable incidences of postoperative lymph nodal upstaging.…”
Section: Discussionsupporting
confidence: 92%
“…The robotic thoracic approach is in full development, with clear indications for resection in lung cancer (37) , and even the esophageal approach has been internationally agreed upon (38) . In 2020, Durand et al (39) published the first study of robotic lobectomy in seven pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…The more precise dissection afforded by the improved 3-dimensional visualization with the robot may be associated with less tissue trauma and less cytokine release. Similarly, it has been argued that the robotic-assisted thoracic surgery (RATS) approach is associated with a more complete lymphadenectomy and thus potentially reduced oncologic burden, which may not only be associated with a lesser inflammatory state, but also a reduced recurrence rate, however, data regarding this phenomenon is not yet conclusive (4,(14)(15)(16)(17)(18)(19)(20).…”
Section: Original Articlementioning
confidence: 99%